The effect of paper coatings containing biopolymer binder and different natural pigments on printability - ÖZCAN, ARİF; URAL, ELİF; ARMAN KANDIRMAZ, EMİNE (De Gruyter Open Ltd, 2021)
Paper is an environmentally friendly, recyclable material whose main material is cellulose, which can be obtained from all kinds of trees and plants, used as writing, printing and packaging material. Due to its structural properties, papers are not resistant to temperature and humidity, as well as problems with ink transfer with its porous structure and experienced negative printability properties. In recent years, especially the growth of the packaging industry has increased the demand for papers with improved printability properties. In order to obtain better printability properties from papers, some processes can be performed in paper production, as well as some surface treatments after production. These processes are paper coating, sizing and calendering. Paper coatings are generally water-dispersed coating solutions with one or more pigments, binders and certain additives to improve the desired properties. With these processes, by filling the gaps between the pores of the paper, a shapely and smooth surface is obtained and good printability is obtained together with the optical and physical properties of the papers. In this study, the interactions and printability properties of different types of pigments with xanthan gum binder were investigated by preparing paper coating formulations using calcium carbonate, barite and talc pigments and xanthan gum as binder. As a result, xanthan is a good coating binder and CaCO3 from the compared pigments is the most suitable compared to the other 2 pigments, considering all the studied areas. © 2021 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: barite; calcium carbonate; paper coating; printability; xanthan gum